2019
DOI: 10.5812/jkums.84103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Resistance Training on Biochemical Markers of Myocardial Injury (cTnT, cTnI, CK-MB) in Non-Athlete Women

Abstract: Background: The purpose of this study was to evaluate the effects of acute resistance training on changes in biochemical markers of myocardial injury (cTnT, cTnI, CK-MB) in non-athlete women. Methods: In this study, 18 healthy young women with a mean age (23.41 years) and body fat percent (21.62) participated voluntarily. Untrained women performed 7 resistance exercises at 70% 1RM in 3 sets and 10 repetitions. Rest interval between sets was 2 minutes. Blood samples were obtained before, immediately, 1, 24, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous research on the CK-MB response to physical exercise has shown an increase in CK-MB levels during and after both prolonged endurance activities [37,42], short bouts of high-intensity effort [24,27], and resistance training [43]. However, there have been a few instances where studies reported no change or even a reduction in CK-MB activity post-exercise compared to resting levels [44].…”
Section: Cardiac Isoenzyme Of Creatine Kinase (Ck-mb)mentioning
confidence: 99%
“…Previous research on the CK-MB response to physical exercise has shown an increase in CK-MB levels during and after both prolonged endurance activities [37,42], short bouts of high-intensity effort [24,27], and resistance training [43]. However, there have been a few instances where studies reported no change or even a reduction in CK-MB activity post-exercise compared to resting levels [44].…”
Section: Cardiac Isoenzyme Of Creatine Kinase (Ck-mb)mentioning
confidence: 99%